Assessing the Common European Asylum System : Discretionary implementation and street-level bureaucracy - Triculescu, Radu-Mihai (International Law E-Books Online, Collection 2025., 2025)
How much discretion do bureaucrats have when deciding who gets refugee status? Where does the boundary between law and practice lie when it comes to asylum in the European Union? In this book, you will find answers to these questions in an exploration of the decision-making context in which policy implementors conduct their work and turn policies into practice. Drawing from the insights of street-level bureaucracy and role-conflict theory, a better understanding is given of how decisions are made by policy implementers in situations of incomplete information or ambiguous policy vision and guidance.